Media and the End of Musharraf Regime in Pakistan: An Analysis of Dawn’s Editorial Page on Judicial and Lal Masjid Crises (2007) - Perveen, Saima; Hassan, Ahmad (Annals of Human and Social Sciences, 2024)
The central aim of this research is to analyze the relation between media and military regimes through Dawn, the most prestigious English newspaper of Pakistan, covering the judicial and Lal masjid crises, the two most decisive events in the political decline of Gen. Musharraf. The military regimes in Pakistan have always been initiated over the argument to safeguard the ‘national integrity’ or ‘national interest’ from the ‘corrupt and incapable politicians’ and end up giving them the government back again; and Gen. Musharraf’s military regime (1999-2008) was not an exception. There could be a list of explicit and implicit reasons that contributed in ending his regime but the two most decisive events were the judicial and Lal masjid crises (2007). Through the qualitative analysis of Dawn’s editorial page this research concludes that Dawn played its role in the restoration of democracy and recommends that free media is crucial for stable democracy.